2022
DOI: 10.3390/pharmacy10010010
|View full text |Cite
|
Sign up to set email alerts
|

Respecting the Patient’s Choice: A Case of Possible Drug-Induced Parkinsonism

Abstract: This report describes a case of likely drug-induced Parkinsonism (DIP) identified by the pharmacist. A 54-year-old female patient was referred by a physician to the pharmacist in a rural, integrated care team for a comprehensive medication review (CMR) to address the patient’s concerns of possible Parkinson’s disease (PD). While PD may occur over the progression of age, medications that affect dopamine transport can also cause DIP, a secondary form of Parkinson’s disease. Although PD and DIP may be clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this reported case, a 54-year-old female patient with suspected Parkinson's disease or drug-induced Parkinsonism (DIP) was advised by a pharmacist to discontinue bupropion, a potential causative drug for DIP; however, the patient chose to continue bupropion due to concerns about depression severity, and recovery outcomes or symptom resolution were not specified in the case, emphasizing the importance of patient preferences in treatment decisions [40].…”
Section: Case Report: Likely Drug-induced Parkinsonism (Dip) and Medi...mentioning
confidence: 99%
“…In this reported case, a 54-year-old female patient with suspected Parkinson's disease or drug-induced Parkinsonism (DIP) was advised by a pharmacist to discontinue bupropion, a potential causative drug for DIP; however, the patient chose to continue bupropion due to concerns about depression severity, and recovery outcomes or symptom resolution were not specified in the case, emphasizing the importance of patient preferences in treatment decisions [40].…”
Section: Case Report: Likely Drug-induced Parkinsonism (Dip) and Medi...mentioning
confidence: 99%
“…Aldarwesh et al, in a study among patients with autoimmune rheumatic disease where hydroxychloroquine has the potential for ocular toxicity, reported a lack of communication between patients and providers about the risk for retinopathy [ 2 ]. On the other hand, a case study reported by Undeberg et al from a rural town in the United States showed the importance of respecting the patient’s decision even when it does not align with the recommendation from the provider [ 3 ].…”
mentioning
confidence: 99%